Low Cost Social Media Based Marketing Communication Mix Analysis On Medium Small Micro Enterprises In Parepare - Aditya Putra Marzuki (Program Studi Ilmu Komunikasi FISIP UM Buton, 2021)
UMKM or Micro, Small and Medium Enterprises (MSME) is one of the important economic sectors in Parepare. MSMEs are the biggest business sector in demand by young people in the city, especially those that engaged in the culinary sector, and they absorb the second largest workforce. Es Duren Caramel and Saogi.ID. are two of them. But with limited capital, they need to use a marketing communication mix that suits their abilities. The alternative is to use social media as a channel for their marketing communication mix. This study uses qualitative research methods with observation and interview techniques to conclude that this two MSME are using the WhatsApp and Instagram application to support the marketing and sales of their products. It is their preferred choice for advertising and marketing. There are several advantages of social media which later become the reason why MSME in general need to use social media as a communication mix for their marketing, and few challenges. In the future, these two MSME have great potential to be more intensive and efficient in utilizing social media as a marketing communication mix platform. However, their owners need to broaden their creativity in creating content related to their products in order to attract more potential consumers. They also need to maintain a more personal relationship with their customers to ensure their costumers loyalty and transform them from being just a consumer, into an advertising agent for these MSME’s products on their respective social media.